Association between dietary fat quality indices with anthropometric measurements in children and adolescents - Maedeh Mozafarinia; Motahar Heidari-Beni; Behnood Abbasi; Roya Kelishadi (BMC, 2022)
Abstract Background The association between anthropometric measures and dietary fat quality indices is unclear in pediatric age groups. The present study aimed to assess the association between dietary lipophilic index (LI) and thrombogenic index (TI) as dietary fat quality indices with anthropometric measurements in children and adolescents. Method This nationwide cross-sectional study was conducted on 4323 students aged 6-18 years that were selected by multistage cluster sampling from 31 provinces of Iran. Dietary intake was collected using a validated food frequency questionnaire and dietary LI and TI were calculated by formula. Data on anthropometric measures were collected by standard protocols. Results The multivariate regression analysis revealed that TI and LI had inverse association with neck circumference Z-score (β = 0.11, p = 0.013 and β = 0.12 p = 0.006, respectively). There was a positive correlation between LI with height Z-score (β = 0.12, 95% CI: 0.01, p = 0.009). However, there was no significant association between LI and TI with other anthropometric indices (P > 0.05). Conclusion The quality of dietary fats was associated with some anthropometric indices. Further large-scale studies are required to highlight the importance of dietary fat quality indices in relation to cardio-metabolic risk factors in pediatric age groups. Reducing intake of saturated fatty acids, increasing consumption of monounsaturated fatty acids and a balanced intake of omega-3 and omega-6 to reduce the risk of cardiovascular diseases risk factors are recommended.